2013
DOI: 10.1155/2013/181564
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Bacterial Keratitis at a Tertiary Eye Care Centre in India

Abstract: Aim. To report the aetiological spectrum and susceptibility patterns of bacteria isolated from patients with corneal ulceration. Method. The microbiological data of all patients with suspected infectious corneal ulceration who presented to the ocular microbiology service at this centre between 2005 and 2012 were reviewed retrospectively. Result. Microorganisms were recovered from 1665 (77%) of the 2170 ulcers. Bacterial isolates accounted for 1205 of the organisms isolated. The most common bacterial pathogens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 51 publications
2
63
1
5
Order By: Relevance
“…Staphylococcus aureus (68.75%) was the predominant isolate among the Gram positive bacterial. This observation is comparable to studies by Kaliamurthy et al, (2013) The present study revealed Pseudomonas aeruginosa (54.54%) as the most isolated organism among the Gram negative bacterial causes which is in accordance with that reported by Sirikul et al, (2008) and Keshav et al, (2008).…”
Section: Resultssupporting
confidence: 93%
“…Staphylococcus aureus (68.75%) was the predominant isolate among the Gram positive bacterial. This observation is comparable to studies by Kaliamurthy et al, (2013) The present study revealed Pseudomonas aeruginosa (54.54%) as the most isolated organism among the Gram negative bacterial causes which is in accordance with that reported by Sirikul et al, (2008) and Keshav et al, (2008).…”
Section: Resultssupporting
confidence: 93%
“…In contrast, other studies reported P. aeruginosa as the major isolate Tesfaye et al, 2013). Another study concluded that S. aureus are the most common bacterial pathogens isolated in keratitis (Kaliamurthy et al, 2013). This may be due to inter-population variations and environmental dissimilarities in different countries (Janumala et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Bacterial keratitis is another entity of ocular infections that might follow corneal epithelial barrier disruption due to injury or trauma with subsequent ulceration and infiltration of inflammatory cells (Kaliamurthy et al, 2013 (Rahimi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…86 Staphylococcus aureus Although studies consistently report Staphylococcus spp. as some of the commonest causes of bacterial keratitis, [90][91][92] contact with the organisms infrequently results in infection. A study by Moreau et al, 93 in which S. aureus was topically applied to scarified rabbit eyes resulted in bacterial killing and identified a role for phospholipase A2 in the tear film as Figure 2 Immune recognition of Pseudomonas aeruginosa molecular patterns.…”
Section: Pattern Recognition Mechanisms Activated By Microbial Pathogmentioning
confidence: 99%